Evaluasi Rekurensi Laparoskopi-assisted Ligasi Ekstraperitoneal dengan Penggunaan IV Catheher 18G pada Pengobatan Hernia Inguinalis Anak - Septry Larissa; Jon Efendi; Budi Pratama Afnoyan (Jurnal Kesehatan, 2020)
Treatment of pediatric inguinal hernia can be done with conventional and laparoscopy methods. Laparoscopic percutaneous extraperitoneal ligation closes the internal inguinal ring by making sutures that are knotted by the extraperitoneum and implanted in the subcutaneous tissue. The rate of recurrence and postoperative complications are still a major concern. Division of pediatric surgery at Dr. M.Djamil Hospital Padang made modifications using an 18G intravenous catheter that was bent to form an angle of 100-150. This study aims to determine the success of laparoscopic herniotomy with modification performed by recurrence rate. This study is a retrospective analytic design method. Data was taken from the medical record status of pediatric inguinal hernia patients undergoing laparoscopic herniotomy at RSUP Dr. M.Djamil Padang from January 2018 -December 2019. Data were analyzed by crosstabulation using the Fisher test. Recurrence was seen in 7,4% of patients (5/68 patients). Three cases in boys and 2 cases in girls. Two cases in the age group ≤1 year and 3 cases in the age group >1 year. One case in the weight group ≤10 kg and 4 cases in the bodyweight >10 kg. Three recurrent cases appeared on the right side and 2 cases on the left side. There were no differences in the incidence of recurrence after laparoscopic-assisted extraperitoneal ligation with intravenous catheter 18G as needle puncture according to age, sex, body weight, and location of the hernia.